Rule of Law in Transitional Democracies: Political Challenges to Legal Reform and Institutional Integrity (Journal of Asian Development Studies, 2025)
Rule of law is a vital pillar for democratic consolidation in transitional democracies, but it is highly contested and highly fragile in practice. This paper considers the political obstacles of legal reform and institutional integrity in Pakistan, a country that illustrates the continued contradictions between state law and effective elite power. The research uses a mixed methods approach combining expert interviews, documentary analysis and institutional performance data to show entrenched patterns of political resistance, judicial politicization and institutional capture. Findings demonstrate that while certain key reform initiatives (i.e., judicial appointment reforms, anti-corruption efforts, media freedom protections) have been significantly weakened by political elites eager to keep control of the state institutions, country conditions necessary for reform efforts have largely remained unchanged. At the same time, civil society actors seeking to defend the rule of law are subjected to mounting repression, and the efforts of international actors to promote meaningful reform have been only limited and selective. The central place of domestic political dynamics in determining rule of law outcomes is highlighted, and integrated, politically informed strategies requiring more than engineering technical legal fixes are recommended. Overall, Pakistan's experience also provides a useful set of observations on why legal reform in transitional democracies too often fails to meet its own aims, and how more effective and sustainable paths toward institutional integrity may be hewn.